I have the following differential equation from a Bellman equation ;

$\displaystyle V\left(s\right)=e^{-rt_{0}\left(s\right)}V\left(S_{2}\right)$ for $s<s_{2}$

In calculations, authors (of the paper that I read) found the general solution in a following way ;

$\displaystyle V\left(s\right)=e^{-rt_{0}\left(s\right)V\left(S_{2}\right)}$

Where they have defined $t_{0}^{'}(s) = -\frac{1}{G(s)}$

Some hints ? or how can I find this general form ?

Thanks in advance.


Just put the $V$'s on one side $$\frac{V'(s)}{V(s)} = \frac{r}{G(s)}$$ and integrate from $s$ to $s_2$ $$\int_s^{s_2} \frac{V'}{V} = \int_s^{s_2} \frac{r}{G}$$ which comes out to $$\ln V(s_2) - \ln V(s) = r t_0(s)$$ where $t_0(s)$ is defined as $$t_0(s) = \int_s^{s_2} \frac{1}{G}.$$ It follows that $$\ln V(s) = -rt_0(s) + \ln V(s_2)$$ which upon exponentiation gives you $$V(s) = e^{-r t_0(s)} V(s_2).$$

  • $\begingroup$ Thank you so much for the clear presentation. $\endgroup$ – optimal control Feb 21 '15 at 18:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.